Relationship Between Lighting Intensity and Eye Fatigue in Workers of the Weaving Industry Central in Dalangan Tawangsari Village, Sukoharjo - Susi Purnama Afrilia; Iik Sartika; Wartini Wartini; Nur Ani (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Eye fatigue is a common condition often experienced by workers in the textile industry when their eyes feel very tired due to prolonged and continuous use in low light conditions. Among textile workers in Dalangan Village, Tawangsari, Sukoharjo, 100% of the 10 respondents experienced eye fatigue due to insufficient lighting intensity that did not meet the standard (300 Lux). This study aims to investigate the relationship between lighting intensity and eye fatigue among textile workers in the central textile industry in Dalangan Village, Tawangsari, Sukoharjo. This is a quantitative study using observational analysis with a cross-sectional approach. Lighting intensity was measured using a lighting measurement observation sheet with a Lux Meter, while eye fatigue was measured using a questionnaire. The study population consisted of 35 workers, and the sample was selected using total sampling. Based on the results of the chi-square test analysis, a significant relationship was found between lighting and eye fatigue among textile workers, with a p-value of <0.05 and a p-value of 0.039. The analysis yielded a PR value of 0.727, meaning that respondents with inadequate lighting have a 0.727 times higher risk of experiencing eye fatigue compared to respondents with adequate lighting. We recommend that weaving workers pay more attention to eye health and ensure that the lighting levels used comply with standards.